The cytogenetics of the telosomic series in the semi-dwarf bread wheat cultivar `Pavon 76' - Prins, Renee (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1991.